From Student Satisfaction to Impact : Approaching Impact Evaluation in the Context of Methodological Constraints. - Leece, Rhonda; Rueckert, Caroline; Madden, Daniel (Student Success v.13 n.2 p.51-58 https://doi.org/10.5204/ssj.2339, 2022)
This study investigated the impact of Queensland University of Technology (QUT) student engagement with co-curricular services in 2020. With limited institutional data, it is often not possible to gauge the cumulative impact of all retention and teaching activities, and while any one support activity cannot carry the weight of improving student outcomes, it is important to consider the impact of each as a contributing factor. We asked ourselves: How exactly do we determine how students’ connection to services is impacting learning? How do they connect to wider university expectations such as widening participation initiatives or retention activities? And how do we use evaluative strategies productively to mature our service design so that we can move beyond “satisfaction” to “impact”? Despite methodological constraints, converging lines of evidence indicate that engagement with services in 2020 had a small, but statistically significant, positive impact on grade point average (GPA), progression, and retention. [Abstract]